ECHOES OF CHANGE: TRANSFORMATIVE NARRATIVES IN CONTEMPORARY TRIBAL LITERATURE WITH SPECIAL REFERENCE TO THE ADIVASI WILL NOT DANCE: STORIES, THE BLACK HILL, AND KOCHARETHI: THE ARAYA WOMAN - Jangir, Priyanka; Kumar, Anupam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study delves into the intricate dynamics of narratives within tribal contexts, examining how narratives undergo change over time and mirror transformative experiences. Tribal communities have been impacted by globalization, cultural shifts, and individual authorial voices by following the trajectory from traditional tribal narratives to contemporary expressions. This present study focuses on contemporary tribal narratives analyzing particularly three chief works of great tribal writers; The Adivasi Will not Dance: Stories by Hansda Sowvendra Shekhar, The Black Hill by Mamang Dai, and Kocharethi: The Araya Woman by Narayan. Their narratives provide a forum for discussing the intricacies of transition, protecting cultural identities from contemporary influences, and advancing knowledge of the dynamic changes occurring within tribal communities. The study’s conclusion not only highlights the vital role that Contemporary tribal literature plays in promoting comprehension, adaptability, and cultural continuity amidst transitions, but it also celebrates the vibrancy of this genre through a thorough examination of themes and authorial perspectives. It also advocates for the inclusion of diverse tribal perspectives in the global discourse to contribute to a more nuanced portrayal of these experience.